Rehardening capacity in the shoots and buds of three European pear (Pyrus communis [L.]) cultivars following a warm spell in midwinter - Dongxia, Wu; Pauliina, Palonen; Iiris, Lettojärvi; Sanna, Finni; Tuuli, Haikonen; Jaana, Luoranen; Tapani, Repo (Elsevier, 2020)
traits that affect the survival, growth and productivity of the European pear (Pyrus communis [L.]) cultivars in northern countries. The frost hardiness (FH) of shoots of three pear cultivars were studied by a series of freezing tests, after sampling in natural conditions, after dehardening in a growth chamber at 5 °C for 3–4 days (D1) and 16 days (D2), and then after rehardening at −7 °C for 5–7 days (R1 and R2). The FH was assessed by a differential thermal analysis (DTA) to measure the low temperature exotherm (LTE) of shoots, by relative electrolyte leakage (REL) of shoots and by visual damage scoring (VD) of shoots and buds. According to the DTA, the FH of the cultivars varied between −38 °C (‘Conference’ in D2) and −41 °C (‘Pepi’ in R2). The shoots of the cultivar ‘Pepi’ and ‘Conference’ had the highest and the lowest FH, respectively, in all conditions and methods. All the cultivars had the lowest shoot FH after dehardening in either D1 (between −26 °C and −30 °C by REL and between −28 °C and −30 °C by VD) or D2 (between −38 °C and −40 °C by DTA), and the highest FH after rehardening (R1) preceded by D1 (between −30 °C and −34 °C by REL, and between −29 °C and −32 °C by VD). After the dehardening in D1, the buds did not reharden but continued to deharden (the average FH by VD−24.5 °C). In the forcing conditions, bud growth was resumed most rapidly in ‘Conference’, indicating a shallower dormancy in this cultivar than in ‘Pepi’ or ‘Clara Frijs’. We conclude that the pear cultivars responded to temperature changes in mid-winter, but less than expected, and the responses were similar in all cultivars.
Keywords: Climate acclimation; dormancy; Frost hardiness; resilience; Species distribution